Predictive Value of the Respiratory Variation in Inferior Vena Cava Diameter for Ventilated Children With Septic Shock - Zihong Xiong; Zihong Xiong; Guoying Zhang; Qin Zhou; Bing Lu; Xuemei Zheng; Mengjun Wu; Yi Qu (Frontiers Media S.A., 2022)
ObjectivesThis study aimed to investigate the predictive utility of respiratory variations of inferior vena cava diameters on fluid responsiveness in children with septic shock.DesignA prospective observational single-center study.SettingA pediatric intensive care unit in a tertiary hospital in China.ParticipantsPatients with sepsis shock who require invasive mechanical ventilation were recruited between 1 December 2017 and 1 November 2021.Interventions and MeasurementsVolume expansion (VE) was induced by a 30-min infusion of 20 ml/kg of normal saline. Hemodynamics indexes were obtained through bedside transthoracic echocardiography (TTE) measurement and calculation.ResultsA total of 86 patients were enrolled in this study, among them, 45 patients (52.3%) were considered to be non-responders (NR), with an increase in stroke volume variation (SVV) <15% after VE. Multivariate logistic analysis showed that ΔIVC (adjusted OR = 1.615, 95% CI 1.092-2.215, p = 0.012) was the significant predictor associated with the fluid responsiveness. The area under the ROC of ΔIVC was 0.922 (95% CI: 0.829-1.000, p < 0.01), and the cutoff value of ΔIVC used to predict fluid responsiveness was 28.5%, with a sensitivity and specificity of 95.4 and 68.5%, respectively.ConclusionsThe ΔIVC was found to have a potential value in predicting fluid responsiveness in mechanically ventilated children with septic shock.